Effect Emotional Fatigue on Job Satisfaction East Lampung Mini Market employees - Eka Pariyanti; Tukasno Tukasno; Rinnanik Rinnanik (International Journal of Ecma Science, 2021)
Dissatisfied employees because the server is too heavily charged in a short time causes a person to experience emotional distress and emotional separation. This condition will eventually cause emotional victims. This study aims at the Effects of Emotional Fatigue on Job Satisfaction of East Lampung Mini Market Employees. Respondents in the study were employees of a mini-market in East Java, meaning 89 people. Data analysis used simple linear regression analysis. The results showed that emotional exhaustion had a negative effect on the job satisfaction of minimarket employees in East Lampung.